2002
DOI: 10.1097/00005537-200202000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Demographics in Patients With Spasmodic Dysphonia

Abstract: The majority of patients with spasmodic dysphonia are girls and women. A significantly higher incidence of childhood viral illness was found in the patients with spasmodic dysphonia. Patients with spasmodic dysphonia had a significant incidence of both essential tremor and writer's cramp but no history of major illness or other neurological disorder. There appear to be no significant environmental or hereditary patterns in the etiology of spasmodic dysphonia. Stress or viral infection may induce the onset of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
103
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(113 citation statements)
references
References 31 publications
10
103
0
Order By: Relevance
“…Most scholars recently believe that this disease stems from neurodegenerative diseases [10], as classified by the National Institute of Neurological Disorders and Stroke (NINDS). In [24] reported a female predominance of 79 % (134 cases) out of a total population of 168 spasmodic dysphonia patients, which is consistent with previous reports [6].…”
Section: Introductionsupporting
confidence: 90%
“…Most scholars recently believe that this disease stems from neurodegenerative diseases [10], as classified by the National Institute of Neurological Disorders and Stroke (NINDS). In [24] reported a female predominance of 79 % (134 cases) out of a total population of 168 spasmodic dysphonia patients, which is consistent with previous reports [6].…”
Section: Introductionsupporting
confidence: 90%
“…However, in light of existing information, no other part of the body is affected in the majority of patients with SD (7). The disease is usually observed in adults and in women (2,5,7).…”
Section: Introductionmentioning
confidence: 98%
“…The disease is usually observed in adults and in women (2,5,7). According to the study of Schweinfurth et al (7), the disease is observed between the ages of 13-71 years. It was also reported that upper respiratory tract infection or stressful conditions may be triggered in some patients (7).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, scoliosis could simply be the manifestation of axial dystonia, which precedes the development of adult-onset cervical dystonia. Measles, mumps, or upper respiratory tract infections appear to be associated with the onset of spasmodic dysphonia (Schweinfurth et al, 2002). Defazio and colleagues (1999) also reported that prior head or face trauma with loss of consciousness was a risk factor for the spread of blepharospasm.…”
Section: Inciting Factors Of Primary Dystoniamentioning
confidence: 99%
“…Trauma to the PNS and CNS (Schott, 1985;Lee et al, 1994;Sankhla et al, 1998;Hollinger and Burgunder, 2000;Hummel and Lucking, 2001), drugs (Remington et al, 1990;Khanna et al, 1992;van Harten et al, 1998;van Harten et al, 1999), neurotoxins (Liu et al, 1992;He et al, 1995;Johnson et al, 2000), and stroke (Krystkowiak et al, 1998;Alarcon et al, 2004) are known causes of secondary dystonia. Environmental factors also correlate with the onset of primary adult-onset dystonias (Chen and Hallett, 1998;Schweinfurth et al, 2002;Defazio et al, 2003). Because DYT1 mutation carriers demonstrate variable phenotypes from primary generalized dystonia to adult-onset focal dystonia, DYT1 dystonia and sporadic adult-onset dystonia may share common environmental risk factors (Leube et al, 1999;Grundmann et al, 2003).…”
Section: Introductionmentioning
confidence: 99%